Cardiac commitment driven by MyoD expression in pericardial stem cells - Zhao, Jianfeng; Rui, Limei; Ouyang, Weili; Hao, Yingcai; Liu, Yusong; Tang, Jianfeng; Ding, Zheheng; Teng, Zenghui; Liu, Xueqing; Zhu, Hongtao; Ding, Zhaoping (Frontiers in Cell and Developmental Biology, 2024)
Cellular therapy holds immerse promises to remuscularize the damaged myocardium but practically hindered by limited allogeneic sources of cardiac-committed cells that engraft stably in the recipient heart after transplantation. Here, we demonstrate that the pericardial tissue harbors myogenic stem cells (pSC) that are activated in response to inflammatory signaling after myocardial infarction (MI). The pSC derived from the MI rats (MI-pSC) show in vivo and in vitro cardiac commitment characterized by Tnnt2 expression (cardiac specific) and formation of rhythmic contraction in culture. Bulk RNA-seq analysis reveals significant up-regulation of a panel of genes related to cardiac/myogenic differentiation, paracrine factors, and extracellular matrix in the activated pSC in comparison to the control pSC (Sham-pSC). Notably, we define MyoD as a key factor that governs the process of cardiac commitment as siRNA-mediated MyoD gene silencing results in a significant reduction of myogenic potential. Injection of the cardiaccommitted cells into the infarcted rat heart leads to long-term survival and stable engraftment in the recipient myocardium. Therefore, these findings point to pericardial myogenic progenitors as an attracting candidate for cardiac cell-based therapy to re-muscularize the damaged myocardium.